Emi sources from microwave electron device - Nikitenko, A. N.; Vasyanovich, A. V. (Published by Institute of Telecommunication, 1996)
Theoretical and experimental studies of spurious in crossed-field devices is described. Ions of residual gases in vacuum tubes are responsible for oscillations. These oscillations affect the electromagnetic oscillation in those tubes. Thus both the breadth and the concentration of output spectrum from crossed-field devices take place.The theoretical study was proved by experimental tests.
Keywords: crossed-field divices; experimental studies; theretical studies; oscilation; output spectrum